Development of a trajectory following vehicle control model - Uzunsoy, Erdem; Erkilic, Veysel (SAGE PUBLICATIONS LTD, 2016)
Determination of the handling properties of a vehicle may be restrictive in some situations. A vehicle model coupled with a driver model may be necessary and even unavoidable to analyse the real road behaviour in the most basic form. Therefore, a fuzzy logic-based controller has been investigated for potential application in modelling driver. Using some particular and limited number of information from characteristics of human driving operation, the model aims to provide any flexible vehicle path reliably. It generates the vehicle's trajectory through a number of specified points through which the vehicle must pass. The controller was modified to account for peripheral vision characteristic of human eye, as an input. The simulation is carried out in the MATLAB(C) programming environment using a Simulink(C) vehicle model. Both longitudinal and lateral controls were applied in the study. This article adds novel approaches to the limited existing published work on driver steering model using fuzzy logic.
Keywords: Vehicle handling dynamics; fuzzy control; driver model; preview control; peripheral vision; DRIVER STEERING CONTROL; PERIPHERAL-VISION; BEHAVIOR; Thermodynamics; Engineering